2016
DOI: 10.18632/oncotarget.10538
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses autophagy in type 2 diabetic osteoporosis

Abstract: Type 2 diabetes mellitus is often complicated by osteoporosis, a process which may involve osteoblast autophagy. As melatonin suppresses autophagy under certain conditions, we its investigated the effects on bone autophagy during diabetes. We first assessed different body parameters in a diabetic rat model treated with various concentrations of melatonin. Dynamic biomechanicalmeasurements, bone organization hard slice dyeing and micro-CT were used to observe the rat bone microstructure, and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 60 publications
2
48
0
Order By: Relevance
“…Many studies have suggested that an excessive dose (1–100 μM) of melatonin could alleviate foreigner antigen‐induced negative nonspecific responses and inflammatory cytokines, including TNF‐α and IL‐1β, which helped to inhibit the acceleration of bone loss (Lian et al, ; Liu et al, ; Ping et al, ). However, Zhang et al found that a lower concentration of melatonin played a more beneficial role (50 mg·kg −1 was better than 100 mg·kg −1 ) in improving bone microstructure in type 2 diabetic osteoporosis rats by regulating bone immunity (Zhang et al, ). Our work confirmed that the anti‐inflammatory effect of melatonin in osteoporotic mice functioned in a concentration‐dependent manner by suppressing serum TNF‐α (Figure f).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that an excessive dose (1–100 μM) of melatonin could alleviate foreigner antigen‐induced negative nonspecific responses and inflammatory cytokines, including TNF‐α and IL‐1β, which helped to inhibit the acceleration of bone loss (Lian et al, ; Liu et al, ; Ping et al, ). However, Zhang et al found that a lower concentration of melatonin played a more beneficial role (50 mg·kg −1 was better than 100 mg·kg −1 ) in improving bone microstructure in type 2 diabetic osteoporosis rats by regulating bone immunity (Zhang et al, ). Our work confirmed that the anti‐inflammatory effect of melatonin in osteoporotic mice functioned in a concentration‐dependent manner by suppressing serum TNF‐α (Figure f).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been documented to regulate autophagy in various cell types; however, its effect on EPCs was not uniform. Melatonin was reported to promote autophagy in diabetic cardiomyopathy, peripheral neuropathy, and to suppress autophagy in type 2 diabetic osteoporosis . However, how melatonin modulates autophagy in EPCs is still unclear: studies in articular chondrocytes have not shown that melatonin may regulate autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin also enhances osteogenesis and suppresses autophagy in osteoblasts cultured with high glucose levels (10 μmol/L was better than 1 mmol/L). This suggests that melatonin may lower the level of autophagy in osteoblasts and delay diabetes‐induced osteoporosis by inhibiting the ERK signaling pathway . Trabecular thickness, trabecular area, and cortical thickness in rats showed a remarkable decrease after ovariectomy.…”
Section: Melatonin Acts As a Protective Agent Against Osteoporosismentioning
confidence: 93%
“…This suggests that melatonin may lower the level of autophagy in osteoblasts and delay diabetes-induced osteoporosis by inhibiting the ERK signaling pathway. 117 Trabecular thickness, trabecular area, and cortical thickness in rats showed a remarkable decrease after ovariectomy. However, administration of melatonin improved these indices.…”
Section: Animal Experimentsmentioning
confidence: 95%